A narrative review of deep learning applications in sports performance analysis: current practices, challenges, and future directionsA narrative review of deep learning applications in sports performance analysis: current practices, challenges, and future directions - Jia, Y.; Abdullah, N. A.; Eliza, H.; Lu, Q.; Si, D.; Guo, H.; Wang, W. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The integration of deep learning techniques into sports performance analysis has significantly advanced athlete monitoring, motion tracking, and predictive modelling. These advancements have significantly improved the ability to assess performance, optimize training strategies, and reduce injury risks. However, despite notable progress, challenges remain in standardizing methodologies, ensuring model reliability, and enhancing real-time application across various sports disciplines.